RETRACTED: Synthesis of dynamic object control systems based on quantum calculation methods - Usmanov K.I.; Yakubova N.S.; Maksudova A.I.; Islomova F.K.; Ungbayeva D.U. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001